Outcome of Open Versus Closed Reduction of Unilateral Mandibular Sub-Condylar Fracture: Open Versus Closed Reduction of Unilateral Mandibular Sub-Condylar Fracture - Kanwal, Sidra; Shahzad, Muhammad; Hamza, Ameer; Sanober, Aamna; Akbar, Awais; Channa, Mansoor Ahmed (Pakistan Journal of Health Sciences, 2025)
Condylar fractures are among the most common types in the maxillofacial area, yet their optimal treatment approach remains debated. Objectives: To compare occlusion and mouth opening between open and closed reduction for unilateral mandibular sub-condylar fractures in adults. Methods: This quasi-experimental study was conducted on 68 patients in Jamshoro using a non-probability sampling technique. Patients aged 18–50 years with unilateral non-comminuted sub-condylar fractures within 48 hours and sufficient dentition for fixation were included, while those with bilateral fractures, undisplaced condyles, or other exclusion criteria were excluded. Participants were divided into two groups: Group A underwent closed reduction with maxillomandibular fixation, and Group B underwent open reduction with internal fixation using titanium mini-plates under general anesthesia. Occlusion, range of motion, and mouth opening were evaluated at 3-month follow-ups. Results: Pre-operative assessments showed limited mouth opening (15–20 mm) in 97.1% and 100%, poor occlusion in 100%, and poor range of motion in 100% of patients in both groups. Post-operatively, mouth opening improved to 20–30 mm in 8.8% vs. 67.6% and 30–45 mm in 73.5% vs. 85.3%. Good occlusion improved to 58.8%, 88.2%, and 97.1% in Group A vs. 82.4%, 94.1%, and 100% in Group B over 1, 2, and 3 months, respectively. Range of motion also improved, reaching 94.1% vs. 100% by the 3rd month. Conclusions: It was concluded that open reduction with internal fixation was a superior therapeutic option compared to closed reduction for unilateral mandibular sub-condylar fractures